Screening for antimicrobial-resistant Gram-negative bacteria in hospitalised patients, and risk of progression from colonisation to infection: Systematic review. Issue 2 (February 2022) - Arzilli, Guglielmo; Scardina, Giuditta; Casigliani, Virginia; Petri, Davide; Porretta, Andrea; Moi, Marco; Lucenteforte, Ersilia; Rello, Jordi; Lopalco, Pierluigi; Baggiani, Angelo; Privitera, Gaetano Pierpaolo; Tavoschi, Lara
Highlights: The burden of AMR-GNB has emerged as an important health care-associated problem. AMR-GNB colonisation and infection are associated with high morbidity and mortality. Prevalence of AMR-GNB carriage at hospital admission was consistent across studies. The risk of acquiring AMR-GNB colonisation during hospital stay is considerable (9%). The risk of progression to infection amongst AMR-GNB colonised patients was high (11%). Abstract: Background: Transmission of antimicrobial-resistant Gram-negative bacteria (AMR-GNB) amongst hospitalised patients can lead to new cases of carriage, infection and outbreaks, hence the need for early carrier identification. We aim to explore two key elements that may guide control policies for colonisation/infection in hospital settings: screening practices on admission to hospital wards and risk of developing infection from colonisation. Methods: We searched on PubMed, Scopus and Cochrane databases for studies published from 2010 up to 2021 reporting on adult patients hospitalised in high-income countries. Results: The search retrieved 11, 853 articles. After screening, 100 studies were included. Combining target patient groups and setting type, we identified six screening approaches. The most reported approach was all admitted patients to high-risk (HR) wards (49.4%). The overall prevalence of AMR-GNB was 13.8% (95%CI 9.3–19.0) with significant differences across regions and time. Risk of progression to infection amongst colonised patients was 11.0% (95%CI 8.0–14.3) and varied according to setting and pathogens' group ( p value<0.0001), with higher values reported for Klebsiella species (18.1%; 95%CI 8.9–29.3). Conclusions: While providing a comprehensive overview of the screening approaches, our study underlines the considerable burden of AMR-GNB colonisation and risk of progression to infection in hospitals by pathogen, setting and time.